Validation of organ culture in colonic adaptation to surgical manipulation. Issue 9 (September 1991) - Appleton, G V; Wheeler, E E; Challacombe, D N; Williamson, R C
Abstract : Valuable information on intestinal adaptation can be gained by using the technique of organ culture to measure the crypt cell production rate. It is not known, however, whether the production rate in organ culture accurately represent that in vivo. Colonic crypt cell production rate, determined by a standard method in vivo, was compared with that in vitro in organ culture in 56 rats. Extensive jejunoileal bypass was used to stimulate colonic hyperplasia, and colonic defunction (by transverse colostomy) led to hypoplasia. There were no differences in crypt cell production rates between in vivo and in vitro groups in normal colon (4.62 (0.39) v 4.80 (0.23) cells/crypt/hour), after 80% jejuno-ileal bypass (7.81 (0.71) v 6.75 (0.72) cells/crypt/hour), or after defunction (2.11 (0.39) v 1.81 (0.35) cells/crypt/hour). Adapting colonic mucosa does not undergo appreciable readaptation in vitro in short term organ culture (10-24 hours). Crypt cell production rate results obtained in man probably reflect in vivo values.